BEBERAPA FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT KEPATUHAN BEROBAT PADA PASIEN HIPERTENSI - Sitorus, Jenti; Nainggolan, Elfrida (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Epidemiological trends show that the number of people with hypertension continues to increase every year, along with changes in lifestyle, high salt and fat diets, low physical activity, and increasing obesity rates. The purpose of this study was to determine several factors associated with the level of treatment compliance in patients with hypertension. The study design used in this study was cross-sectional. The study was conducted in the working area of the Soposurung Community Health Center. The study was conducted in December 2024. The population consisted of all hypertensive patients in Sibolahotang Village, Balige District, totaling 198 people. The sample consisted of 66 people. The sampling technique used purposive sampling. The research instrument used a research questionnaire. Data analysis was performed using univariate and bivariate analysis. The results showed a relationship between occupation (p value: 0.04) and family support (p value: 0.00) with treatment compliance in hypertensive patients. It is recommended that the Community Health Center provide education and socialization about hypertension and compliance in taking hypertension medication in the form of leaflets, brochures, or directly in a language that is easier for hypertensive patients to understand. Keywords: Family Support, Hypertension, Work